2018
DOI: 10.1111/febs.14356
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural insights into a thermostable cellobiohydrolase from Myceliophthora thermophila

Abstract: The atomic coordinates and structural factors of MtCel7A have been deposited in the Protein Data Bank with accession number 5W11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 91 publications
(135 reference statements)
5
18
0
1
Order By: Relevance
“…From a structural perspective, the entire CtCel7_CD region houses the classical curved β-sandwich constructed with two largely antiparallel β-sheets in an equatorial elongated substrate-binding tunnel, which is in accordance with the archetypal feature of GH7 CBH structures (Figure 2A; Momeni et al, 2014;Borisova et al, 2015). This predominant structural feature allows CtCel7 to act along cellulose chains without affecting the substrate configuration and clip off numerous cellobiose units before detaching from the substrate (Kadowaki et al, 2018), which is indispensable to its prominent hydrolysis efficiency on highly crystalline cellulose (Payne et al, 2015;Taylor et al, 2018). Combined with the homologous sequence alignment, the results identified the catalytic triad residues Glu213 (nucleophile), Asp215 and Glu218 (acid/base) in CtCel7 and revealed that these are embedded in the binding tunnel, where two cellotriose molecules (−5 to −3 and −1 to +2 subsites, respectively) are involved in coordinated interactions with adjacent residues located within 5 Å via hydrogen bonding (Figures 2B,C).…”
Section: Sequence Analysis Of Ctcel7supporting
confidence: 64%
See 3 more Smart Citations
“…From a structural perspective, the entire CtCel7_CD region houses the classical curved β-sandwich constructed with two largely antiparallel β-sheets in an equatorial elongated substrate-binding tunnel, which is in accordance with the archetypal feature of GH7 CBH structures (Figure 2A; Momeni et al, 2014;Borisova et al, 2015). This predominant structural feature allows CtCel7 to act along cellulose chains without affecting the substrate configuration and clip off numerous cellobiose units before detaching from the substrate (Kadowaki et al, 2018), which is indispensable to its prominent hydrolysis efficiency on highly crystalline cellulose (Payne et al, 2015;Taylor et al, 2018). Combined with the homologous sequence alignment, the results identified the catalytic triad residues Glu213 (nucleophile), Asp215 and Glu218 (acid/base) in CtCel7 and revealed that these are embedded in the binding tunnel, where two cellotriose molecules (−5 to −3 and −1 to +2 subsites, respectively) are involved in coordinated interactions with adjacent residues located within 5 Å via hydrogen bonding (Figures 2B,C).…”
Section: Sequence Analysis Of Ctcel7supporting
confidence: 64%
“…The purified protein CtCel7 was confirmed by MALDI-TOF/TOF (Supplementary Figure S1) and SDS-PAGE (Figure 3). As estimated from the SDS-PAGE results, the apparent homogeneity had a higher molecular weight (approximately 73 kDa) than the predicted homogeneity (56 kDa), which can most likely be ascribed to glycosylation (Hua et al, 2018;Kadowaki et al, 2018). In addition, the glycoprotein staining analysis corroborated that CtCel7 was a glycoprotein (Figure 3).…”
Section: Cloning Expression and Purification Of The Recombinant Ctcementioning
confidence: 80%
See 2 more Smart Citations
“…SAXSMoW is a simple to use, fast and relatively precise method for determinations of the molecular weight of proteins in dilute solution (Guttman et al 2013). The program has been widely used during the last decade to determine the molecular weights of many proteins with different shapes and forms, including globular, elongated, flexible and glycosylated proteins, and also protein complexes (Ferreira et al 2011;Zheng et al 2012;Carter et al 2015;Gruszka et al 2015;Chang et al 2018;de Araújo et al 2018;Glauninger et al 2018;Kadowaki et al 2018).…”
Section: Saxsmow2 Software For Data Processingmentioning
confidence: 99%